FAKTOR-FAKTOR YANG MEMENGARUHI PENGUNGKAPAN INTERNET FINANCIAL REPORTING (Media Riset Akuntansi, 2022)
This study aims to examine the effect of profitability, leverage, liquidity, company size, listing age, and public ownership of shares on internet financial reporting disclosures. The population in this study are various industrial sector manufacturing companies listed on the Indonesia Stock Exchange in the 2016- 2018 period, amounting to 144 companies. The sampling technique used was purposive sampling method. Based on these methods a sample of 87 companies was obtained. The data method used is multiple linear regression method using SPSS version 24 software. The results show that profitability, liquidity, company size, and public ownership affect the disclosure of internet financial reporting, while leverage and listing age do not affect the disclosure of internet financial reporting